Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Review: 30



Work Step by Step

60$y^{3}$-39$y^{2}$+6y= 3y(20$y^{2}$-13$y^{}$+2)=3y(20$y^{2}$-5$y^{}$-8y+2)= 3y[5y(4y-1)-2(4y-1)]=3y(5y-2)(4y-1)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.